Salivary alterations in type 1 diabetes mellitus patients: Salivary glucose could be noninvasive tool for monitoring diabetes mellitus - Syed Shahbaz; Girish Katti; Sreenivas Rao Ghali; Chandrika Katti; Darshan D Diwakar; Vijay Guduba (Wolters Kluwer Medknow Publications, 2014)
Background: Diabetes mellitus (DM) is an endocrine disease characterized by hyperglycemia, the pathogenic mechanisms by which hyperglycemia arises differ widely. Monitoring people with diabetes involve repeated estimations of plasma glucose either by finger pricks or by intravenous blood sampling. Hence, a noninvasive procedure for glucose measurements would be most precious under the circumstances. Aims: (1) To evaluate salivary glucose, total protein and albumin in type 1 DM (T1DM) patients and to compare with healthy nondiabetic control group. (2) To compare and correlate serum and salivary glucose levels in patients with T1DM. Study Design: This study consisted of 30 T1DM patients and 30 controls. All subjects were subjected to the serum glucose, salivary glucose, and total protein and albumin estimations. Materials and Methods: Glucose estimations were done by glucose oxidase-peroxidase method, total protein estimations were done by Biuret method, end point and albumin estimations were done by bromocresol green dye method, end point. All the estimations were performed using an autoanalyzer. Statistical Analysis: Mean and standard deviation, Student's t-test and Karl Pearson correlation co-efficient were calculated. All these statistical analyses were performed by using SPSS 11.5 software. Results: The results showed elevated levels of salivary glucose, total protein and albumin in T1DM group compared to healthy controls. Further the levels of serum and salivary glucose in T1DM patients were significantly correlated. Conclusion: There are definite changes in salivary composition with increased levels of salivary glucose, total protein and albumin in T1DM patients compared with healthy controls. Salivary glucose could be used for monitoring of DM.